Grape pomace flour ameliorates Pseudomonas aeruginosa-induced bioenergetic dysfunction in gills of grass carp - Baldissera M.D. (2019)
© 2019 Elsevier B.V.Grape pomace is a by-product of the winemaking process, rich in bioactive compounds such as resveratrol and has antioxidant and antimicrobial properties. Recent evidence has demonstrated the protective effects of grape against impairment of the phosphoryl transfer network, a system linked to energetic homeostasis of high-energy phosphoryl transfer, to maintain energetic balance. Also, Pseudomonas aeruginosa infection in fish has been related to severe impairment of the branchial phosphoryl transfer network via inhibition of creatine kinase (CK), adenylate kinase (AK) and pyruvate kinase (PK) activities. Thus, the aim of this study was to evaluate whether dietary supplementation with grape pomace flour (GPF) is able to reduce or prevent the impairment of cellular energetic homeostasis in grass carp (Ctenopharyngodon idella) experimentally infected by P. aeruginosa. Branchial CK (cytosolic and mitochondrial), AK, and PK activities were lower in infected animals on day 15 post-infection (PI) compared to uninfected fish, while lactate dehydrogenase (LDH) activity was higher. Branchial reactive oxygen species (ROS), thiobarbituric acid reactive substances (TBARS), lipid oxidation (LOOH) and protein carbonylation levels were higher, while the level of non-proteic (NPSH) and proteic (PSH) thiols was lower in infected fish on day 15 PI, as compared to uninfected fish. The use of 300 mg of GPF/kg of feed was able to ameliorate the activities of CK, AK, PK, and LDH as compared to infected fish, but their activities remained different from the control group. On the other hand, dietary supplementation with 300 mg of GPF/kg of feed was able to prevent all alterations linked to oxidative damage elicited by disease. Based on this evidence, inhibition of the phosphoryl transfer network may contribute to the impairment of intracellular energetic communication between cellular ATP synthesis and consumption and is mediated by oxidative damage in the gills of fish infected by P. aeruginosa. The use of 300 mg of GPF/kg of feed exerted protective effects on branchial energetic metabolism linked to ATP metabolism by reducing the impairment in cellular energetic homeostasis; its effects can be mediated by the prevention of SH group oxidation.